Digital Transformation, Media Attention, and Tax Avoidance: A Study of Indonesian Multinationals - Hidayatulloh, Taufiq; Tanzil, Nanny Dewi; Priyono, Agus Puji (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: The objective of this research is to determine the influence of corporate digital transformation and media attention on tax avoidance practices by multinational corporations (MNC) in Indonesia. Methodology/approach: This quantitative study utilizes panel data regression to examine the influence of corporate digital transformation and media attention on tax avoidance. The sample consists of 97 multinational corporations listed on the Indonesia Stock Exchange. Data was sourced from annual reports and Google News search results, covering the period from 2019 to 2023. Results/findings: Counterintuitively, the findings reveal a positive correlation between corporate digital transformation and tax avoidance, while media attention exerts no significant influence. This suggests that companies are leveraging technology to develop more sophisticated tax planning strategies, maximizing potential tax savings. Meanwhile, media scrutiny appears to be a secondary consideration in corporate tax strategy formulation. Limitations: The study is constrained by its focus on IDX-listed multinational corporations and the exclusion of unprofitable firms. Furthermore, the reliance on Google News for media attention data and the lack of sentiment analysis limit the scope of the findings. Contribution: This research advances the understanding of the complex relationship between digital transformation, media attention, and tax avoidance. By exploring the empirical evidence and offering policy recommendations, this study contributes to both the theoretical and practical dimensions of tax research. Novelty: This study provides a pioneering analysis of the relationship between digital transformation, media attention, and tax avoidance among multinational corporations operating in Indonesia.